Peranan Manajemen Operasional dalam Meningkatkan Kinerja Perusahaan Ritel di PT Tsamaniya Amanah Mandiri - Alhilwa, Raissalma Queena; Kusuma, Yanda Bara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
"Retail is detail" said James Gulliver, which means that in a retail company every detail must be considered. Operations management is one of the keys to the successful arrangement of every detail of the activities in it so that the company's performance becomes organized. That way as a retail company that has been moving for decades, PT Tsamaniya Amanah Mandiri continues to develop the operational management strategies they use. In this study, the research focus lies on the effect of retail operations management on company performance. Data and information were collected through interviews with relevant personnel, analysis of internal and external data, and direct observation of the processes taking place at PT Tsamaniya Amanah Mandiri. Thereafter, analysis and interpretation are conducted on the data that has been collected, with the aim of gaining an in-depth understanding of the emerging findings. The methods used may involve statistical analysis, modeling, and theoretical approaches to support conclusions.